Thiophenol detection using an AIE fluorescent probe through self-assembly with TPE-based glycoclusters. Issue 41 (4th October 2019) - Dong, Lei; Chen, Guo-Rong; He, Xiao-Peng; Vidal, Sébastien
Abstract : While the original probe (TD-1 ) was not efficient enough, supramolecular self-assembly with a glycocluster (TPE2S or TPE4S ) could restore and enhance its fluorescence detection properties. Abstract : We describe a novel green-emitting tetraphenylethylene-dicyanomethylene-4 H -pyran (TPE-DCM) based fluorescent probe (TD-1 ). Conjugating TPE and DCM moieties allowed TD-1 to display high selectivity for thiophenol with excellent AIE properties in aqueous solution. Nevertheless, the poor water solubility of the hydrophobic structure resulted in a weak and unstable emission intensity. The non-covalent self-assembly of TD-1 with a TPE glycocluster (TPE2S) led to a largely improved water solubility producing a reliable and stable sensing system. The corresponding glyco-probe could sensitively detect exogenous thiophenol concentrations in PBS buffer or environmental water samples.